Complexes of Ni(ii) and Cu(ii) with small peptides: deciding whether to deprotonate. Issue 38 (20th September 2016) - Dunbar, Robert C.; Martens, Jonathan; Berden, Giel; Oomens, Jos
Abstract : Infrared multiple photon dissociation (IRMPD) spectroscopy differentiates two binding modes (iminol versus charge solvated) for Ni(ii ) bound to model peptides. Abstract : The observed variety of metal-ion complexation sites offered by peptides reflects a basic tension between charge solvation of the ion by Lewis-basic chelating groups versus amide nitrogen deprotonation and formation of metal–nitrogen bonds. Gas-phase models of metal-ion coordination can illuminate the factors governing this choice in condensed-phase proteins and enzymes. Here, structures of gas-phase complexes of Ni(ii ) and Cu(ii ) with tri- and tetra-peptide ligands are mapped out using a combination of Infrared Multiple Photon Dissociation (IRMPD) spectroscopy and density functional theory (DFT) computations. The two binding modes give distinctive IRMPD signatures, particularly in the diagnostic region 1500–1550 cm −1 . Previous observations have suggested that Ni(ii ) complexes preferentially show the iminol rearrangement pattern (Im) giving low-spin square-planar geometries with metal-ion bonds to deprotonated amide nitrogens. In contrast, alkaline earth metal ion complexes prefer amide carbonyl oxygens chelating the metal ion with pyramidal geometry (charge-solvation, CS). Surprisingly, it is shown here that the Gly4 complexes are CS bound, in contrast with the expectation of Im binding. It is suggested that CS binding is actually a normal Ni(ii ) and Cu(ii ) binding mode to simple peptides lacking participating side chains. Three factors are suggested to influence the choice between CS and Im binding patterns: (1) presence of an accessible side-chain Lewis-basic proton interaction site (FGGF, FGG and HAA complexes); (2) short chain length of the peptide leading to a shortage of accessible carbonyl oxygen sites for CS binding, (AAA, FGG and HAA complexes); (3) outright deprotonation of the ligand giving net negatively charged Im[Ni 2+ (Gly4 –3H + )] − and Im[Ni 2+ (Ala3 –3H + )] − complexes, which have a triply-deprotonated ligand. IRMPD spectra of [Cu 2+ Gly4 ] 2+ and [Cu 2+ (Gly4 –3H + )] − complexes suggest that their structures are similar to their Ni 2+ analogs.